KONSTRUKSI CITRA PEREMPUAN DALAM BERITA KASUS KEKERASAN SEKSUAL DI TEMPO.CO DAN REPUBLIKA.CO.ID - Cahyani, Arum Tri; Mau, Muliadi; Muh. Akbar (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
Online media, as a communication tool that is increasingly accessed by the public, plays a significant role in shaping social discourse and public perceptions of sexual violence. This study aims to analyse how online media outlets Tempo.co and Republika.co.id construct images of women in their reporting on cases of sexual violence. Using a qualitative approach and framing analysis, this study explores how the two media outlets frame narratives of sexual violence, both in their portrayal of victims and perpetrators and in their contextualization of the events. The analysis reveals that the media portrays women in a subordinate position within the patriarchal structure, where women are often depicted as weak and dependent victims of violence. Illustrations in the news, such as images of women being grabbed or emphasis on the clothing worn by women, reinforce gender stereotypes and the position of women in patriarchal culture. Although there are efforts to protect victims in news reports, the existing narratives still show gender bias and paternalistic stereotypes, in which women are portrayed as sexual objects. This study is expected to contribute to communication and media studies, as well as provide recommendations on how the media can report sexual violence in a more fair and responsible manner and provide a deeper understanding of the social construction of sexual violence in the public sphere.     Keywords: Framing Analysis; Online Media; Sexual Violence; Women's Image